Comparison of intravascular optical frequency domain imaging versus intravascular ultrasound during balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension. Issue 7 (18th March 2016) - Ikeda, Nobutaka; Kubota, Shuji; Okazaki, Toru; Hara, Hisao; Hiroi, Yukio
Abstract : Objectives: The aims of this study are (1) to evaluate the safety and feasibility of using optical frequency domain imaging (OFDI) during balloon pulmonary angioplasty (BPA) procedures, (2) to assess the correlations between the vessel area (VA) and luminal area (LA) obtained by OFDI and intravascular ultrasound (IVUS), and (3) to compare inter‐ and intra‐observer variability among measurements taken from OFDI and IVUS images. Background: The BPA in patients with chronic thromboembolic pulmonary hypertension (CTEPH) is an evolving procedure. Methods: Twenty‐three consecutive attempts of pair of OFDI and IVUS during BPA were evaluated. All complications that occurred during‐BPA and up to 48 hr post‐BPA were recorded. Using side branches as landmarks, 48 pairs of regions were chosen to compare measurements of VA and LA. Results: OFDI images can be obtained without any procedurally related complications. Although the VA and LA measurements obtained by OFDI were smaller than those obtained by IVUS, high correlations were found (VA: r = 0.78, P < 0.0001 and LA: r = 0.75, P < 0.0001). Less inter‐ and intra‐observer variability was found when using measurements taken from OFDI versus IVUS images. Conclusions: OFDI during BPA was safe and feasible. The reproducibility of OFDI imaging was excellent and offered a favorable addition to the BPA procedures. © 2016 The Authors Catheterization and Cardiovascular Interventions Published by Wiley Periodicals, Inc.